Pelatihan Pembuatan Blog Sebagai Media Informasi Interaktid Pada UKKT RW. 06 Kelurahan Tegal Parang Jakarta Selatan - Nilawati, Lala; Ariyati, Indah; Hikmah, Noer; Brawijaya, Herlambang (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
One of the changes in the field of communication can be seen from the speed at which people obtain information. The speed of obtaining this information is influenced by the emergence of communication technology facilities, namely computers and the internet. Internet technology can make it easier for people to communicate, as well as convey information more effectively and accurately. The delivery of interactive information within the Karang Taruna RW.06 Work Unit organization, Tegal Parang Subdistrict, South Jakarta, has not been optimally felt by the community. This community service activity takes the form of training in creating blogs as an interactive information medium, to improve communication and information within an organization. The target training participants are members and the Karang Taruna RW.06 Work Unit. The training is carried out face to face with the hope that the material presented will be easier for the training participants to understand and put into practice. Participants are given material about the definition and function of a blog, how to create one and how to manage the blog so that it becomes an interactive information medium. As a result of this training, participants have a simple blog, as a form of digital communication to send, receive and share information with the public.